Public communication strategies on prevention and cannabis: Eye tracking and facial expression - Martínez Martínez, Luz; Piqueiras , Paloma (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Cannabis is the most widely consumed illegal substance in the world (United Nations Office on Drugs and Crime, 2021), which represents a public health problem. Therefore, this research proposes the analysis of the relationship between cognition and emotion applied to information about cannabis, from the conception of persuasive communication and the application of neurocommunication tools. The findings: 1) identify consumption patterns and perceptions about cannabis among young people; 2) evaluate the implicit responses associated with the use of different types of frame and; 3) study the interaction produced by different communication strategies.